Analysis of Risk Impact on Transportation Costs & Employee Performance - Mantinu, Ramadani Al; Eka Lestiani, Melia; Kusdanu Waskito, Saptono (Riviera Publishing, 2025)
Companies everywhere will face problems. Some of these problems are caused by internal and external problems of the Company. These problems can result in small or large losses to the Company. The instrument of this research is quantitative research with data study analysis, namely observation and literature study. In this study, the Fault Tree Analyst approach will be used. The application of this method begins with defining the problem, describing the graphical model, finding the minimum cut set, conducting a qualitative analysis, and conducting quantitative analysis. This research is a research development of the Enterprise Risk Management method. In previous research, using ERM only focused on identifying and evaluating risks through a qualitative approach based on the perception and experience of internal stakeholders on potential operational disruptions. However, this study develops this method by integrating a quantitative and systematic Fault Tree Analysis (FTA) approach in mapping the root causes of delivery inaccuracy. If in the ERM approach the risk is identified in general based on the probability-impact matrix, then in the FTA approach, the risk is further traced to the level of components and basic events, so as to be able to provide a more detailed picture of the contribution of each causative factor. The problems faced in this company focus on risk control related to the transportation of product delivery in this company. To strengthen the results of this study, the author added recommendations for proposed improvements. The results of the study using Fault Tree show that the dominant risks in this company are extreme distribution delays, work accidents that occur during work, and damage to transport vehicles. The problems in this study focus on risk control related to product delivery transportation.